A study to establish a formula for predicting the mesiodistal size of permanent canines and premolars for use in space analysis - Nguyen , Le Minh Trang; Le , Thi Khanh Huyen; Nguyen , Ngoc Tam Dan; Nguyen , Thi My Linh (Tạp chí Y Dược Huế, 2025)
Background: This study was conducted to determine the correlation between the mesiodistal width of the mandibular incisor group and that of the permanent canines and premolars, thereby establishing a predictive formula for permanent tooth eruption space, applicable in space analysis. Materials and methods: A cross-sectional descriptive study was carried out on 200 students of Hue University of Medicine and Pharmacy. Measurements were taken directly on dental casts. The correlation between the mesiodistal widths of the mandibular incisors and the permanent canines and premolars was assessed using Pearson’s correlation coefficient. Based on this, a linear regression model was developed to estimate the measurements. Results: The predictive formulas for the maxillary and mandibular arches are: Maxillary: Y = 0.51X + 10.25; Mandibular: Y = 0.54X + 8.74; Where: X = Mesiodistal width of the mandibular incisor group; Y = Mesiodistal width of the canine and premolar group in both arches. Conclusion: In clinical practice, the established regression equations can be used to estimate the eruption space of permanent teeth (canines and premolars) based on the existing mesiodistal width of the mandibular incisors.